BIOCHEMICAL MARKERS OF BONE TISSUE METABOLISM INFLUENCE ON VULNERABILITY OF ATHEROSCLEROTIC LESIONS - Ya. N. Polonskaya; E. V. Kashtanova; I. S. Murashov; A. M. Volkov; A. M. Chernyavskiy; Yu. I. Ragino (Российский кардиологический журнал)
Aim. To assess some of biochemical markers of bone tissue metabolism, in vessel wall in males with coronary atherosclerosis; to evaluate the influence of these markers on vulnerability of atherosclerotic lesion and to figure out the specifics of their spread among unstable plaques of various kinds.Material and methods. Totally, 65 males included at the age 46-79 y. o., admitted to the Clinics of E. N. Meshalkin Novosibirsk Scientific-Research Institute of Circulation Pathology for coronary bypass surgery. During operation, an endarterectomy was performed of coronary arteries. Each specimen of endarterectomy was symmetrically divided to fragments for histological and biochemical studies. By the results of histological analysis, in 193 specimens we found: 19 fragments of intact intima, 102 stable, 72 unstable plaques. Then the types of unstable plaques were established: 1) lipids’; 2) inflammatory-erosive; 3) distrophic-necrotic. In homogenates of the fragments we assessed: osteoprotegerin, calcitonin, osteocalcin, cholesterol. Statistics was done with SPSS (13.0).Results. By the results of the performed histology, in unstable plaques there was higher level of calcification comparing to stable plaques. Biochemical studies showed increased levels of calcitonin and osteocalcin. If to assess the diverse types of unstable plaques, the highest level of these parameters was found in distrophic-necrotic plaques; lowest amount of calcitonin and osteocalcin was found in inflammatory-erosive type. Content of cholesterol in stable and unstable atherosclerotic lesions was about 4 times higher (p<0,01) in comparison with intact intima. Relation of cholesterol with calcitonin and osteocalcin was found, as well.Conclusion. The data shows that increased osteoprotegerin aids the stabilization of lesion, and calcitonin and osteocalcin might be markers of plaque instability, caused by increased calcification.